Strategi Komunikasi Dinas Pariwisata Provinsi Sumatera Barat dalam Meningkatkan Daya Tarik Wisatawan di Masa New Normal Melalui Media Youtube - Rahmadya Helsi Putri; Ria Edlina (LPPM Universitas Dharma Andalas, 2022)
Communication helps tourism marketing in various marketing elements, communication plays a role both in communication media and communication content. In communication media, there are various kinds of communication media as marketing channels, destinations, accessibility and media channels for human resources and tourism institutions. In a modern perspective, the components of marketing, destinations, accessibility, human resources, and tourism institutions, as well as the existing elements become a unified tourism product in a destination that is packaged in a destination brand, so that destinations, accessibility, marketing, human resources and tourism institutions become a unified product. tourist. Therefore, this study was conducted to determine the communication strategy of the West Sumatra Tourism Office in conducting branding in the New Normal era using Youtube. This study uses qualitative methods to describe communication strategies using youtube while data collection techniques use observation and in-depth interviews. Interviews were conducted with employees of the West Sumatra Tourism Office, especially the creative team. The results of the study show that there are 4 stages of using youtube so that they can be used until they experience problems and are used sustainably, namely: 1. Emergence stage where youtube was formed due to competition from the Ministry of Home Affairs, 2. Coalescence stage merging the use of youtube media with other media such as Instagram and Facebook, 3. The Formalization Stage ( Bureaucratization ) scheduled postings on YouTube media such as 3 times a week, 4. The Result or Decline stage ( Decline ) there is no special budget for the operation of the Tourism Office youtube account. The communication strategy carried out is to form a special team for managing media to run effectively, as well as aggressively uploading videos to increase the attention and interest of tourists on YouTube, there is also a description of the object that is being broadcast. Keywords : communication strategy, attractiveness, tourist attraction, new normal, youtube.